Breeding schemes: what are they, how to formalize them, and how to improve them? - Covarrubias Pazaran, Giovanny Eduardo; Gebeyehu, Z.; Gemenet, D.; Werner, Christian R.; Labroo, Marlee Rose; Sirak, S.; Coaldrake, Peter; Rabbi, I.Y.; Kayondo, S.I.; Parkes, Elizabeth Y.; Kanju, E.; Mbanjo, E.; et al. (Frontiers Media, 2022)
Formalized breeding schemes are a key component of breeding program design and a gateway to conducting plant breeding as a quantitative process. Unfortunately, breeding schemes are rarely defined, expressed in a quantifiable format, or stored in a database. Furthermore, the continuous review and improvement of breeding schemes is not routinely conducted in many breeding programs. Given the rapid development of novel breeding methodologies, it is important to adopt a philosophy of continuous improvement regarding breeding scheme design. Here, we discuss terms and definitions that are relevant to formalizing breeding pipelines, market segments and breeding schemes, and we present a software tool, Breeding Pipeline Manager, that can be used to formalize and continuously improve breeding schemes. In addition, we detail the use of continuous improvement methods and tools such as genetic simulation through a case study in the International Institute of Tropical Agriculture (IITA) Cassava east-Africa pipeline. We successfully deploy these tools and methods to optimize the program size as well as allocation of resources to the number of parents used, number of crosses made, and number of progeny produced. We propose a structured approach to improve breeding schemes which will help to sustain the rates of response to selection and help to deliver better products to farmers and consumers.